Patients with Multiple Drug-Resistant Pulmonary Tuberculosis at Dr. Mohammad Hoesin General Hospital, Palembang: Association of Body Mass Index on Drug Side Effects - Ahmad, Zen; Elzan Zulqad Maulana; Alif Fathurrachman; Dwi Indira; Linda Andriani; Sudarto; Rouly Pasaribu; Ahmad Rasyid (RSUP Dr Moh Hoesin Palembang, 2023)
Patients with Multiple Drug-Resistant Pulmonary Tuberculosis at Dr. Mohammad Hoesin Palembang: Association of Body Mass Index on Drug Side Effects. Tuberculosis (TB) is an infectious disease transmitted by acid-resistant bacteria, namely, Mycobacterium tuberculosis (MTb). TB enters the respiratory tract and infects the lungs, and it can spread to other organs both hematogenously and lymphogenously. Pulmonary TB is the most common occurrence. Based on resistance, there are 2 types of pulmonary TB infection: drug-sensitive and drug-resistant. Multiple drug-resistant pulmonary TB (MDR-TB) is a type of pulmonary TB bacteria that is resistant or immune to rifampicin and/or isoniazid treatment. In the treatment of pulmonary TB, MDR uses a multi-drug combination therapy regimen in which each drug has both major and minor side effects. One of the risk factors for side effects is body mass index (BMI). In this study, conducted using a retrospective descriptive method during the 2019–2021 period at Dr. Mohammad Hoesin General Hospital Palembang, 52 subjects met the inclusion and exclusion criteria. 33 subjects (63.5%) were under weight, and 19 subjects (36.5%) were normoweight. Of the 52 subjects, 27 experienced minor ESO and 25 experienced major ESO. The most common major ESO is hearing loss, with 12 events, and in the underweight group, with 10 events. The most common minor ESO was nausea, which occurred 14 times in the overweight group and 9 times in the underweight group. The chi square test showed that there was a significant relationship between underweight BMI and the incidence of major ESO with a p value of 0.029 and an odds ratio (OR) of 3.67x. We concluded that a low body mass index had a 3.67x effect compared to a normal BMI on the increased incidence of major side effects of anti-tuberculosis drugs in MDR-TB patients at Dr. Mohammad Hoesin General Hospital Palembang.